Epidemiological profile of reported cases of exogenous poisoning in the State of Piauí, Brazil (Research, Society and Development, 2021)
This study aimed to describe the epidemiological profile of exogenous intoxications reported in the state of Piauí - Brazil between the years 2013 to 2017. An exploratory, epidemiological and descriptive research was carried out with a cross-sectional, quantitative and retrospective approach, the data were taken from of the National System of Notifiable Diseases (SINAN) of the Unified Health System (SUS), the profile showed a predominance of females, aged between 20-39 years old, incomplete elementary school, the most frequent toxic agent were medicines, circumstances were suicide attempts and evolution with no sequel in most cases. A total of 6,113 cases of poisoning were recorded between the years analyzed. We conclude, with this study, the importance of notifications as a proposal for the implementation of continuous improvements of notifications and the filling of the forms in SINAN, as it will allow us to obtain reliable and consistent data.